1999
DOI: 10.1007/s001070050349
|View full text |Cite
|
Sign up to set email alerts
|

Hexamine hardener behaviour: effects on wood glueing, tannin and other wood adhesives

Abstract: The peculiar behaviour noticed in tannin-based and other wood adhesives when hexamethylenetetramine (hexamine) is used as a hardener is described. When using hexamine as hardener in tannin adhesives, a¯ow problem during hot curing of this adhesive/hardener system and its consequences on adhesive performance is identi®ed. The solution of the tannin/hexamine problem con®rmed and gave a clear theoretical justi®cation for the applied ®nding that under many application conditions hexamine is not a formaldehyde-yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(61 citation statements)
references
References 17 publications
4
57
0
Order By: Relevance
“…The inclusion of the monomeric aminocaproic acid or its oligomers in the tannin-hexamine network can be figured out in many ways. According to the signal of R-CH 2 -O, the more probable hypothesis is that the reactive imines produced from hexamine in alkaline environment react with the carboxylic group of the caprolactam (Pichelin et al 1999). Here, a possible polymer structure is observed (Fig.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The inclusion of the monomeric aminocaproic acid or its oligomers in the tannin-hexamine network can be figured out in many ways. According to the signal of R-CH 2 -O, the more probable hypothesis is that the reactive imines produced from hexamine in alkaline environment react with the carboxylic group of the caprolactam (Pichelin et al 1999). Here, a possible polymer structure is observed (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…A significant breakthrough in the chemistry of flavonoid tannins was that their condensation reactions occurred with similar extent as phenol and resorcinol (Pizzi 1980;Pichelin et al 1999), and therefore, it was possible to oppose the long-standing leaching problem of tannin in the wood preservation field and hence raise this approach to a new level.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the increasing restrictions on the release of volatile organic compounds (VOCs) to the atmosphere, there are decreasing trends from using organic solvents and dispersing media. As indicated in Pichelin et al (1999), any species with a strong negative charge under alkaline condition is capable to render bonded panels of extremely low formaldehyde emission, in other words, the adhesives based on hexamine could reduce the impact of environment of formaldehyde. The results (Pichelin et al, 1999) showed that tannin-hexamine adhesive is a very environmentally-friendly product.…”
Section: Environmental Effectsmentioning
confidence: 99%
“…Hexamine (see Fig. 9B in Chapter 15 of this book) or the cheap methylolated nitroparaffins for example can functionally replace formaldehyde as hardener , Pichelin et al 1999, Trosa & Pizzi 2001, Kim & Kim 2003, Kim et al 2003. In such way, panel boards satisfying the Japanese standard JIS A 5908 (2003) were obtained in laboratory and in industrial trials (Pichelin et al 2006).…”
Section: Tanninsmentioning
confidence: 99%